Muscle-Specific Myosin Heavy Chain Shifts in Response to a Long-Term High Fat/High Sugar Diet and Resveratrol Treatment in Nonhuman Primates - Hyatt, Jon-Philippe K.; Nguyen, Lisa; Hall, Allison E.; Huber, Ashley M.; Kocan, Jessica C.; Mattison, Julie A.; de Cabo, Rafael; LaRocque, Jeannine R.; Talmadge, Robert J. (Frontiers in Physiology, 2016)
Shifts in myosin heavy chain (MHC) expression within skeletal muscle can be induced by a host of stimuli including, but not limited to, physical activity, alterations in neural activity, aging, and diet or obesity. Here, we hypothesized that both age and a long-term (2 year) high fat / high sugar diet (HFS) would induce a slow to fast MHC shift within the plantaris, soleus, and extensor digitorum longus (EDL) muscles from rhesus monkeys. Furthermore, we tested whether supplementation with resveratrol, a naturally occurring compound that has been attributed with augmenting aerobic potential through mitochondrial proliferation, would counteract any diet-induced MHC changes by promoting a fast to slow isoform switch. In general, we found that MHC isoforms were not altered by aging during mid-life. The HFS diet had the largest impact within the soleus muscle where the greatest slow to fast isoform shifts were observed in both mRNA and protein indicators. As expected, long-term resveratrol treatment counteracted, or blunted, these diet-induced shifts within the soleus muscle. The plantaris muscle also demonstrated a fast-to-slow phenotypic response to resveratrol treatment. In conclusion, diet or resveratrol treatment impacts skeletal muscle phenotype in a muscle-specific manner and resveratrol supplementation may be one approach for promoting the fatigue-resistant MHC (type I) isoform especially if its expression is blunted as a result of a long-term high fat/sugar diet.